3D highly isolated 6-port tri-band MIMO antenna system with 360° coverage for 5G IoT applications based machine learning verification - Md Afzalur Rahman; Samir Salem Al-Bawri; Sultan S. Alharbi; Wazie M. Abdulkawi; Noorlindawaty Md Jizat; Mohammad Tariqul Islam; Abdel-Fattah A. Sheta (Scientific Reports)
Abstract A multipurpose antenna system that can handle a broad area of frequencies is crucial in the effort to build up widespread 5G Internet-of-Things (IoT) networks. For fifth-generation Internet-of-things applications, this research introduces a new multi-band antenna that can operate in the sub-6 GHz band (2–7 GHz), Ku-band (13–17.5 GHz), and millimeter wave band (25–39 GHz). The antenna achieves a remarkable three-band operational bandwidth through cleverly integrated slots and parasitic components. Maximum realized gain of 4.3 dBi in the sub-6 GHz band, 5.5 dBi in the Ku-band, and 9.9 dBi in the millimeter wave (mm-wave) band for 3D MIMO setup is ensured. In addition, the machine learning prediction is used to verify the single element realized gain, and the results demonstrate that it performs admirably with an accuracy of more than 89% using the random forest regression model throughout the entire frequency spectrum. A 6-port, one-of-a-kind MIMO design with strong diversity performance is built from the single-element configuration. This 6-port MIMO system uses a new codesign technique to achieve 360-degree coverage in the elevation and azimuth planes, exceptional isolation (21 dB at sub-6 GHz band, 25 dB at the Ku-band, and 30 dB at mm-wave band), and pattern diversity. This MIMO antenna module is a shining example of the future, with the potential to completely alter the state of affairs in terms of 5G IoT connectivity in settings such as smart homes, offices, cities, vehicle-to-everything communications, and broadcast satellite service (BSS).